Is time a pure affection of oneself - Carlos (Estudios de Filosofía, 1991)
Three levels of discussion guide the study of the internal structure of time: the inner sense, the empirical and pure multiplicity, the sensible and the pure affection of oneself. Their distinction and connection permits, on the one hand, to show the impossibility of identifying time with the pure affection of oneself (Heidegger), and, on the other, to see in this affection the presupposition that makes a pure multiplicity out of it, in so far as it is a free and spontaneous activity of the mind [Gemüt], and not of the understanding. In order ro carry out this task,the text centers on the apprehensive syntbesis.